RELASI HIBRIDITAS DAN DUALITAS DALAM TRANSFORMASI BENTENG VREDEBURG DI YOGYAKARTA - Nadhifah, Arina Khansa' (ALUR :Jurnal Arsitektur, 2025)
Vredeburg Fort in Yogyakarta has undergone numerous transformations in both function and meaning over time. Originally serving as a symbol of colonial power in the form of a defensive outpost, it has now shifted into a museum that reflects the struggle for independence. This paper aims to discuss and explain the transformation of Vredeburg Fort based on the theories of hybridity and duality, as well as to explain the relationship between these two theories. The method used in this analysis is a case study, based on literature and visual documentation, which is then compared historically. The results of this analysis reflect a proportional interaction between hybridity and duality in the social, political, and cultural contexts, based on the transformation of space and time, which can be further understood as the true national identity of Indonesia.